Sex differences in normal fetal regional brain apparent diffusion coefficient changes assessed by in utero DWI - Ren, Jing-Ya; Zhu, Ming; Dong, Su-Zhen (Frontiers in Pediatrics, 2024)
OBJECTIVE: There are differences in the vulnerability of male and female fetal brains in their vulnerability to adverse intrauterine exposure, preterm birth, and associated perinatal brain injury. The main objective of this study was to detect any statistical difference in the change of apparent diffusion coefficient (ADC) in intracranial regions of male and female fetuses in the 2nd to 3rd trimester. METHODS: DWI (diffusion-weighted imaging) was performed in 200 fetuses between 20 and 37 gestational ages (GA) with normal results or suspicious abnormalities abnormal results on sonography followed by normal structural MRI. Pairwise ADC values of the regions of interest (ROIs) were manually delineated in either side of the cerebral white matter: frontal (FWM), parietal (PWM), occipital (OWM), temporal (TWM), basal ganglia (BG), thalamus (THA), and cerebellar hemisphere (CBM), as well as a single measurement in the pons. The changes in those values were studied over the gestational range, along with potential sex differences and asymmetries of the cerebral hemispheres. RESULTS: During the 3rd trimester, ADC values in OWM, TWM and CBM were significantly higher in male fetuses than those in females (p<0.05). After correction for False-discovery rates, the difference in CBM was only statistically significant (p= 0.0032). However, the decrease rate of ADC values in male fetuses in cerebral WM (except for frontal), BG, THA, CBM, and pons was higher than that of female fetuses during the 2nd to 3rd trimester. CONCLUSIONS: We have shown some differences in intracranial regional ADC changes between male and female fetuses using utero-DWI during the 2nd to 3rd trimester.